Analisis Hubungan Intellectual Capital dan Struktur Modal: (Studi Pada Perbankan Syariah di BEI Selama Masa Pandemi Covid 19) - Rosita Rosita; Fatlina Zainudin; Heri Susanto; Sari Ramadhani (CV. Ulil Albab Corp, 2022)
This study aims to be able to contribute to providing a view of the condition of the capital structure of Islamic banking in facing economic downturns during the Covid-19 pandemic. The research design is prepared by analyzing the relationship that explores elements of Intellectual Capital (IC) to the capital structure. The Islamic banking data used is quarterly data in the period 2020 and 2021. The results showed that Islamic banking that has IC elements, namely Human Capital Efficiency, Structural Capital Efficiency, Capital Employed Efficiency and High Relational Capital Efficiency, has low financial leverage. This condition is important for Indonesian Islamic banks in controlling the risks of their capital structure. This has the implication that Islamic banking must always maintain the strength of the elemental values in the IC in its operations.